Fabrication of Bilayer Coating of Poly(3,4-ethylenedioxythiophene)-Halloysite/Chitosan and Mg2+/Sr2+-Doped HAP on Titanium Alloy for Biomedical Implant Applications: Physicochemical and In Vitro Biological Performances Studies - Manickam Chozhanathmisra; Dharman Govindaraj; Palanisamy Karthikeyan; Kannaiyan Pandian; Liviu Mitu; Rangappan Rajavel (Journal of Chemistry)
The prime objective of the present work is to develop biocompatible overlayer-deposited titanium alloys to replace already available titanium alloy-based biomaterials for implantation applications. Here, we prefer to use a bilayer coating on titanium alloys instead of single coating. The adhesion and biocompatibility of titanium alloy is improved by coating with a bilayer, for example, PEDOT-HNT/CS-MHA composite using the electrochemical deposition method. Corrosion behavior of the PEDOT-HNT/CS-MHA bilayer composite coating was investigated in the PBS medium by polarization studies. The functional groups, phase purity, surface morphology, and wettability of the PEDOT-HNT/CS-MHA were characterized by various instrumental techniques like FTIR, XRD, SEM, and contact angle techniques. From the above studies, it is proved that PEDOT-HNT/CS-MHA-coated Ti alloy showing a better biocompatibility and corrosion resistance than the PEDOT-HNT-deposited Ti alloy. In addition, the in vitro bactericidal and cell viability studies were also carried out to further confirm the biocompatibility of the protective coating. Hence, the bilayer deposition has shown excellent stability and biocompatibility and can be used for the potential biomaterials for orthopedics applications.